Proyecto de inversión para la implementación de un gimnasio en la Parroquia Malacatos del Cantón Loja - Guamán Maza, Manuel Efrén (2016)
The main objective of this research is "Developing an Investment Project for the Implementation of a Gym in the Parish of Loja Canton Malacatos" idea born as the Development Plan and Zoning Malacatos Parish of Loja Canton suggests that you should build recreational facilities in the parish. For this project set out to develop four specific objectives are: "Establishing a market study in which it is determined; service characteristics, customer characteristics, potential demand, actual demand, effective demand, unsatisfied demand, per-equity annual use, supply, service analysis, channel marketing, price analysis, analysis of promotion and advertising " "Conduct a technical study, in which the macro-location is established, the micro-location, capacity, capacity utilization, service stages, the process flow-gram, level of fitness, machinery and equipment", "Develop a Study Organizational where the legal basis of constitution, organization, functions manual logo, gym, vision, mission and values stipulated", "Making a financial study to determine the feasibility of the project". The methodology used in this project was the scientific, deductive, inductive, mathematical, analytical method and techniques of bibliography, direct observation, survey and interview. The results were: to study the potential market demand of 2379 people, the actual demand for 1642 people and the effective demand for 1625 people, annual supply of 69408 times, sometimes unmet 213342 people per year or 1226. The technical study established that the macro location of the project is the parish of Malacatos, the micro location will be 5 in the Central District of the aforementioned parish, street Colonel Miguel Riofrio between Lauro and Manuel Ignacio Godoy. The installed capacity will be 150.500 services in a year; for the first year 80% of installed capacity, for the second year and 90% for the third onwards 100% of the installed capacity, the services will be 1 hour is used. In organizational study the legal framework was determined, the requirements needed to implement the project, has also developed the structural and functional organization, manual functions, rules, manual labor risk prevention, has developed a logo for the gym and finally a proposed mission, vision and values for the company made. In the financial study the initial investment is $ 50.892,44 was known; the equilibrium point will get when the company uses the 75,56% of its installed capacity and when you get a total income of $ 69.888,09; NPV is $ 33.667,64, the benefit is $ 1,30; IRR is 32,76%, the capital recovery period is 2 years, 7 months and 7 days, the sensitivity of the project is that the company can withstand an increase in costs to 5,47% and in relation to the sensitivity of income, they can decrease to 4,20%, finally the conclusions and recommendations were made.